Noradrenergic modulation of the parallel fiber-Purkinje cell synapse in mouse cerebellum. (February 2015) - Lippiello, Pellegrino; Hoxha, Eriola; Volpicelli, Floriana; Lo Duca, Giuseppina; Tempia, Filippo; Miniaci, Maria Concetta
Abstract: The signals arriving to Purkinje cells via parallel fibers are essential for all tasks in which the cerebellum is involved, including motor control, learning new motor skills and calibration of reflexes. Since learning also requires the activation of adrenergic receptors, we investigated the effects of adrenergic receptor agonists on the main plastic site of the cerebellar cortex, the parallel fiber-Purkinje cell synapse. Here we show that noradrenaline serves as an endogenous ligand for both α1 -and α2 -adrenergic receptors to produce synaptic depression between parallel fibers and Purkinje cells. On the contrary, PF-EPSCs were potentiated by the β-adrenergic receptor agonist isoproterenol. This short-term potentiation was postsynaptically expressed, required protein kinase A, and was mimicked by the β2 -adrenoceptor agonist clenbuterol, suggesting that the β2 -adrenoceptors mediate the noradrenergic facilitation of synaptic transmission between parallel fibers and Purkinje cells. Moreover, β-adrenoceptor activation lowered the threshold for cerebellar long-term potentiation induced by 1 Hz parallel fiber stimulation. The presence of both α and β adrenergic receptors on Purkinje cells suggests the existence of bidirectional mechanisms of regulation allowing the noradrenergic afferents to refine the signals arriving to Purkinje cells at particular arousal states or during learning. Highlights: Noradrenaline depresses the synapse between parallel fibers and Purkinje cells. α1 -and α2 -adrenergic receptor agonists also depress this synapse. Isoproterenol and β2 agonists short-term potentiate this synapse. β agonists lower the threshold for 1 Hz-long-term potentiation.